Reporting on data monitoring committees in neonatal randomised controlled trials is inconsistent. (25th October 2016) - Perrem, LM; Gosling, S; Ravikumar, I; Khashan, AS; Miletin, J; Ryan, CA; Dempsey, E
Abstract: Aim: To evaluate the reported use of data monitoring committees (DMCs), the frequency of interim analysis, prespecified stopping rules and early trial termination in neonatal randomised controlled trials (RCTs). Methods: We reviewed neonatal RCTs published in four high‐impact general medical journals, specifically looking at safety issues including documented involvement of a DMC, stated interim analysis, stopping rules and early trial termination. We searched all journal issues over an 11‐year period (2003–2013) and recorded predefined parameters on each item for RCTs meeting inclusion criteria. Results: Seventy neonatal trials were identified in four general medical journals: Lancet, New England Journal of Medicine (NEJM), British Medical Journal and Journal of American Medical Association. A total of 43 (61.4%) studies reported the presence of a DMC, 36 (51.4%) explicitly mentioned interim analysis, stopping rules were reported in 15 (21.4%) RCTs and seven (10%) trials were terminated early. The NEJM most frequently reported these parameters compared to the other three journals reviewed. Conclusion: While the majority of neonatal RCTs report on DMC involvement and interim analysis, there is still scope for improvement. Clear documentation of safety‐related issues should be a central component of reporting in neonatal trials involving newborn infants.